2021
DOI: 10.1093/plankt/fbab071
|View full text |Cite
|
Sign up to set email alerts
|

Protoplasmic streaming of chloroplasts enables rapid photoacclimation in large diatoms

Abstract: Long-term (2004–2020) studies showed yearly summer/autumn blooms in the NE Black Sea dominated by large (cell volume > 5000 μm3) diatoms (Pseudosolenia calcar-avis and Proboscia alata). This phenomenon is characterized by high (>250 W m−2 photosynthetically active radiation, PAR) insolation, and low phosphorus concentrations (to analytical zero). These diatoms contained >100 chloroplasts per cell, which at low irradiance are evenly distributed throughout the cell. As light increases (to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 87 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…In other words, a rapid growth strategy is implemented in this case [68]. The maximum specific growth rate is characteristic of small diatoms due to the high specific light absorption coefficients, which are several times higher than the same indicator for large diatoms [109]. Comparing Figure 5 we obtained with Figure 1 in the article by Meunier et al (2017), it should be noted that there is a significant difference.…”
Section: Basic Conceptual Schemementioning
confidence: 73%
“…In other words, a rapid growth strategy is implemented in this case [68]. The maximum specific growth rate is characteristic of small diatoms due to the high specific light absorption coefficients, which are several times higher than the same indicator for large diatoms [109]. Comparing Figure 5 we obtained with Figure 1 in the article by Meunier et al (2017), it should be noted that there is a significant difference.…”
Section: Basic Conceptual Schemementioning
confidence: 73%
“…Thus, based on the experimental results, it can be assumed that a typical Black Sea cyclonic eddy, lifting both the nutricline and thermocline, creates conditions close to optimal for this species. The physiological properties of this species, including the ability for rapid photoadaptation and storage of nutrients in a large vacuole (Silkin et al, 2021;Stelmakh, 2022), allow it to grow rapidly, using the increased flow of deep nutrients. The mass development of P. calcar-avis, observed in autumn in mesoscale cyclonic eddies of the Black Sea, confirms this assumption (Mikaelyan et al, 2018(Mikaelyan et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…These medium‐ and large‐celled species have regularly developed in the Black Sea (Mikaelyan et al., 2018). It has been shown that P. calcar‐avis can rapidly photoacclimate to low and high light due to the repackaging of chloroplasts (Silkin et al., 2021). This mechanism allows P. calcar‐avis to avoid photodegradation of pigments at the surface and deploy a photosynthetic antenna at a depth, which determines their ability to form blooms in the UML and the thermocline (Mikaelyan et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a dynamic environment with a deep thermocline, the light intensity varies widely from photoinhibition level in the near-surface layer of water to light limitation at the ST lower boundary. According to another hypothesis, large diatoms can change the specific light absorption coefficient due to moving chloroplasts [12]. This ability allows them to change the amount of energy absorbed depending on the intensity of the light.…”
Section: Annual Dynamics Of Phytoplanktonmentioning
confidence: 99%
“…The classical concepts of regulating the annual dynamics of phytoplankton are based on the change of mixing regimes in the ocean and the associated vertical transport of nutrients [11]. Light intensity can also shift the structure of phytoplankton [12].…”
Section: Introductionmentioning
confidence: 99%